Numerical Simulation of Vapor Flow and Pressure Drop across the Demister of MSF Desalination Plant - Janajreh, Isam (2012)
This paper presents a numerical simulation of the water vapor flow in an MSF flash chamber along with the pressure drop across the demister. The demister is a simple porous blanket of metal wires mesh (usually made of stainless steel wires) which retains liquid droplets entrained by the vapor momentum to enhance the quality of the product water. Two main areas of concern in wire mesh mist eliminators are; (i) the pressure drop and (ii) the mist removal efficiency. The present simulation focuses only on the pressure drop across the demister. The simulation is carried out considering a full scale flashing chamber of a typical operational MSF desalination plant and of a real industrial demister dimensions. The study simulates the demister as porous media flow. It takes into account the vapor velocity, the dimension of the demister, its porosity and wire thickness. The obtained pressure drop was found to be within a reasonable agreement with the published literature data and it follows a trend compatible with Ergun’s equation as well as the empirical correlation of Svendsen.